(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The electronic product industry is currently growing in Indonesia, so this condition causes the market to be more varied and ultimately makes consumers more selective in making purchases. This study aims to determine the effect of customer experience and brand trust on repurchase intention at PT Midea Electronics Indonesia Denpasar Denpasar-Bali Branch. Determination of the sample based on the proportionate random sampling method with a total of 70 people, then data collection was carried out by distributing questionnaires and analyzed using multiple linear regression analysis techniques. The regression results conclude that simultaneously or partially customer experience and brand trust have a significant positive effect on repurchase intention, therefore PT Midea Electronics Indonesia Denpasar Denpasar-Bali Branch needs to design appropriate marketing strategies to increase consumer buying interest in Midea products through increased variable customer experience and brand trust from the Midea brand.